aaCheating are attitudes translated into practices - aaKoo, Grace S.
aaThe first part of the study initiated to find out how Filipino students perceive cheating in its moral sense. The second part was conducted to see how these moral attitudes would stand against actual situation. The question in this research was: what is the relationship between attitude towards cheating and cheating behaviour?
Keywords: aaCheating (Education) -- Philippines; aaAttitude (Psychology) -- Philippines; aaMoral education (Secondary) -- Philippines